The Effect of Abdominal Aortic Aneurysm Size on Endoleak, Secondary Intervention and Overall Survival Following Endovascular Aortic Aneurysm Repair. (July 2021) - Ferrel, Benjamin; Patel, Shiv; Castillo, Antonio; Gryn, Oscar; Franko, Jan; Chew, David
Objective: The purpose of this study was to identify the effect of abdominal aortic aneurysm (AAA) size on endoleak development and secondary intervention after endovascular repair (EVAR), as well as to examine the effect on overall survival and cause of mortality. Methods: Retrospective analysis was performed on all non-ruptured AAA treated by elective EVAR using FDA-approved endografts in our facility from July 2004 to December 2017. Patients were grouped into 3 cohorts based on preoperative aneurysm size: Group I (<5.5 cm), Group II (5.5-6.4 cm), and Group III (≥ 6.5 cm). Occurrences of endoleak, secondary intervention and overall survival underwent univariate and multivariate analysis. Cause of death data on deceased patients was similarly examined. Results: A total of 517 patients were analyzed. There was no difference between size groups in the rate of endoleak (Group I 48/277, 17.3%; Group II 33/160, 20.6%; Group III 18/80, 22.5%; p = 0.46) or time until endoleak development. Univariate analysis showed no difference in the rate of secondary intervention (Group I 36/277, 13.0%; Group II 24/160, 15.0%; Group III 18/80, 22.5%; p = 0.11), time until intervention or number of interventions performed. Multivariate analysis showed an association with shorter time to secondary intervention for both Group III aneurysms (HR 2.03, 95% CI 1.11-3.73; p = 0.02) and female patients (HR 1.79, 95% CI 1.02-3.13; p = 0.04). There was no difference in overall survival, aneurysm-related mortality or overall cause of mortality. Conclusion: AAA diameter prior to EVAR was not associated with any differences in rates of endoleak or secondary intervention, and was not associated with poorer overall survival or greater aneurysm-related mortality. Patients with suitable anatomy for EVAR can be considered for this intervention without concern for increased complications or poorer outcomes related to large aneurysm diameter alone.